An Enhanced Energy Efficient Secure Routing Protocol for MANET - Nippun Kamboj, Dalip,Dr. Munishwar Rai (International Journal of Advanced Science and Technology, 2020)
With growing demand of the wireless network, Mobile Ad hoc Network (MANET) is most widely used platform for data communication. MANET is infrastructure-less network i.e. there is absence of any central administration for carrying out the communication activity. Die to this nature of MANET there are various challenges during communication such as security, Reliability, energy consumption, stability etc. Among various concerns security and energy consumption are most important challenges in the network. The most widely used protocol in the MANET is Ad hoc On demand Distance Vector Routing (AODV). So this research paper emphasizes on improving the security of the existing AODV as well as enhancing the energy conservation of the network. In this research paper Enhanced Energy Efficient Secure-AODV (EEES-AODV) is proposed to build network further efficient. The proposed algorithm is simulated using NS-2.34. Metrics such as Delay, Packet Delivery Ratio (PDR), Throughput and Energy Consumed are compared with the existing protocol.